Glaube und Gesetz - Moritz Deecke (Zeitschrift für Junge Religionswissenschaft)
Messianic Jews can most easily be described as Jews that believe in Jesus as the Jewish Messiah. Those Messianic Jews living in Israel are in a difficult position: on the one hand they are forced to defend themselves against Christian missionaries that attempt to strip them of their »Jewishness«, on the other hand they are targeted by orthodox Jews that perceive them as a threat to the Jewish identity as a whole. The building of an individual and collective Messianic-Jewish identity thus seems paradoxical. This article is focused on the question how Messianic Jews bridge the gap between the antagonistic Jewish and Christian poles. Based on a theory-governed analysis of ten biographical interviews with Messianic Jews in Israel, the author of this article concludes, that they split their religious activities into a decidedly Jewish-appearing practical (and therefore visible) dimension, which is uncomplicated in Israel, and a far less apparent theoretical dimension, dominated by Christian implications which are problematic in the Israeli context, but, however, remain hardly visible.